Counsel and defense counsel immunity - E.I. Gerfanova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The implementation of the immunities of a lawyer and defense counsel in criminal law was long overdue; in the procedural branches of law, the prohibition of their interrogation is, in fact, recognized as axiomatic, established over the centuries, perhaps, from the moment of the more or less formed legal institute. De facto judicial practice, including the European Court of Human Rights and the Constitutional Court of the Russian Federation, recognizes the absolute immunity of these persons. The paper deals with the issues of criminal law and procedural regulation of the institution of lawyer and defender; the content of the terms attorney-client privilege, close relatives, other persons has been disclosed. The relation between these terms has been shown. The behavior of lawyers has been discussed as a problematic issue, because there are only five cases when the criminal immunity is enshrined according to the Criminal Code of the Russian Federation: Pt. 4 of Art. 11; Notes to Art. 2056, 308, 316, and 322. The place of the rule on immunity, the note to Art. 308 of the Criminal Code of the Russian Federation, providing for the liability for refusal to testify has been considered. The immunity and the crime in question are genetically linked: as long as lawyers cannot be interrogated in the presence of the circumstances specified in the criminal procedure and other federal legislation, the refusal to give evidence does not constitute a crime.